2013
DOI: 10.1002/chem.201203737
|View full text |Cite
|
Sign up to set email alerts
|

Core‐Modified meso‐Aryl Hexaphyrins with an Internal Thiophene Bridge: Structure, Aromaticity, and Photodynamics

Abstract: Take the shortcut: The synthesis of core-modified meso aryl hexaphyrins with an internal thiophene bridge is reported. Introduction of the thiophene bridge alters the electronic structure as well as the π-electron circuit, resulting in increases in singlet lifetime (τ(s)) and the two-photon absorption (TPA) cross-section. Furthermore, for the sulfur derivative, the internal bridging thiophene participates in a π-electron conjugation pathway.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 32 publications
(34 citation statements)
references
References 20 publications
0
34
0
Order By: Relevance
“…The free‐base form exhibited a sharp Soret band at 617 nm and Q‐bands at 731 and 915 nm, with a molar absorption coefficient ( ɛ ) for the Soret band in the order of ×10 5 m −1 cm −1 . Comparison of these data with other non‐bridged congeners ( 1 ) and bridged expanded porphyrins ( 3 and 4 ) revealed the following: 1) the non‐bridged [34 π] octaphyrin ( 1 a ) showed a broad absorption spectrum and the ɛ value was in the order of ×10 4 m −1 cm −1 , which was attributed to its non‐aromatic character; 2) the Soret and Q‐bands for compound 5 were red‐shifted compared to those of the bridged derivatives ( 3 and 4 ), which reflected an increase in the number of π electrons in the molecular framework; and 3) the sharp Soret band in compound 5 suggested a single conjugation pathway, as observed in the bridged derivatives ( 3 a , 3 b , 3 d , and 4 b ) . Overall, the Soret and Q‐bands reflected the aromaticity, planarity, and major conjugation pathway in the [34 π] octaphyrin, as observed from NMR spectroscopic analysis.…”
Section: Resultsmentioning
confidence: 91%
See 4 more Smart Citations
“…The free‐base form exhibited a sharp Soret band at 617 nm and Q‐bands at 731 and 915 nm, with a molar absorption coefficient ( ɛ ) for the Soret band in the order of ×10 5 m −1 cm −1 . Comparison of these data with other non‐bridged congeners ( 1 ) and bridged expanded porphyrins ( 3 and 4 ) revealed the following: 1) the non‐bridged [34 π] octaphyrin ( 1 a ) showed a broad absorption spectrum and the ɛ value was in the order of ×10 4 m −1 cm −1 , which was attributed to its non‐aromatic character; 2) the Soret and Q‐bands for compound 5 were red‐shifted compared to those of the bridged derivatives ( 3 and 4 ), which reflected an increase in the number of π electrons in the molecular framework; and 3) the sharp Soret band in compound 5 suggested a single conjugation pathway, as observed in the bridged derivatives ( 3 a , 3 b , 3 d , and 4 b ) . Overall, the Soret and Q‐bands reflected the aromaticity, planarity, and major conjugation pathway in the [34 π] octaphyrin, as observed from NMR spectroscopic analysis.…”
Section: Resultsmentioning
confidence: 91%
“…Furthermore, variable‐temperature 1 H NMR analysis of the free‐base form of compound 5 did not alter the peak position, which reflected the rigidity of the macrocycle (see the Supporting Information, Figure S5). A comparison of these results with non‐bridged [34 π] octaphyrin 1 and bridged derivatives 3 and 4 revealed that compound 1 a adopted a figure‐eight conformation in solution and was non‐aromatic, whereas compound 1 b was aromatic –. On the other hand, bridged derivatives 3 c and 4 a followed a dual‐aromatic conjugation pathway, in which the rest of the bridged derivatives followed a single aromatic conjugation pathway …”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations